Implementation of Value Clarification Technique (VCT) Methods to Civic Education Subject In Improving The Learning Result of Class IV Elementary School Students - Mawardi; Najib Hasan (Jurnal Sekolah Dasar, 2021)
This study aims to improve the activities and learning result of Civics for grade IV elementary school students by using the Value Clarification technique (VCT) learning method. The research method used classroom action research (PTK) model Kemmis and Mc. Taggart. The research was conducted at Jamiatul Khoir Tangerang city. Data were collected through test, observation, and documentation techniques which were then analyzed through qualitative and quantitative techniques. The results showed that there was an increase in Civics learning result as seen from the average value of Civics learning result obtained by students in the pre-cycle was 63.7 in cycle I, namely 75.4 and in cycle II, namely 86.7. Thus the application of the Value Clarification technique (VCT) method in Civics learning for grade IV elementary school students can effectively increase student activity and learning result.